MRI as an aid for diagnosis of infantile neuroaxonal dystrophy - Ishii, M; Tanabe, Y; Goto, M; Sugita, K (No to hattatsu, 1992)
We experienced a 5-year-old girl, who had presented with nystagmus and psychomotor regression since 1 year old. No clinical diagnosis had been made despite various examinations including lysosomal enzymes and muscle biopsy. Her brain magnetic resonance imaging (MRI) revealed increased a T2 signal in bilateral cerebellar hemisphere. Recently this MRI finding was reported as a typical feature of infantile neuroaxonal dystrophy (INAD). Then we performed the second biopsy from her peripheral nerve, and diagnosed her as having INAD. It was suggested that MRI was a useful aid for the diagnosis of INAD.